Food price spiral : causes and consequences - Teng, Paul (2012)
Food prices have been trending upwards. Unchecked increases have social and political repercussions. Speculation on food as a commodity has contributed to the spiral. “Market panic” and “herd mentality” must be checked to avoid volatility.